The Effects of Problem-Based Learning on Fourth-Grade Students’ Critical Thinking and Speaking Skills in English Instruction - Nengah Wardatul Uyun; Padlurrahman Padlurrahman; Muhammad Khairul Wazni (Sumber Belajar Sejahtera, 2026)
This study examines the effects of Problem-Based Learning (PBL) on fourth-grade students’ critical thinking and speaking skills in an elementary English as a Foreign Language (EFL) context. A quasi-experimental design with a pretest–posttest control group was employed, involving 36 students divided into experimental and control groups. Data were collected using a validated multiple-choice test to assess critical thinking and a performance-based rubric to evaluate speaking skills. The data were analyzed using Multivariate Analysis of Variance (MANOVA) and independent sample t-tests. The results of the MANOVA indicated that PBL did not have a statistically significant effect on the combined dependent variables (Wilks’ Λ = 0.968, F = 0.614, p = 0.547). However, univariate analysis revealed a significant effect of PBL on students’ critical thinking skills (p < 0.05), while the effect on speaking skills was not statistically significant. These findings suggest that PBL is more effective in enhancing higher-order cognitive skills than in improving oral communication abilities in elementary EFL learners. This study contributes to the growing body of research on constructivist learning by providing empirical evidence that PBL supports the development of critical thinking skills in young learners. However, the findings also highlight the need for integrating explicit language instruction and scaffolding strategies to improve speaking performance. The study offers important pedagogical implications for designing balanced instructional approaches that address both cognitive and communicative competencies in language learning.